2009
DOI: 10.1021/je900706h
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Dichloromethane on Activated Carbon

Abstract: Adsorption is an economical option for the removal of volatile organic compounds (VOCs) from effluent streams of various industries. Its feasibility depends on the equilibrium and kinetics of the adsorption process. A conventional apparatus for the measurement of adsorption equilibria and kinetics needs dedicated equipment which may not be readily available in all laboratories. To overcome this limitation, in this work adsorption equilibrium of a VOC, namely, dichloromethane, was measured on activated carbon b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…CH 2 Cl 2 as a solvent has been commonly used in paint remover, industrial degreasing, foam production, and so on [17] . This highly volatile solvent even at room temperature has been reported as a cause of chronic toxicity, mutagenicity, and carcinogenicity for living organisms [18] . The triazine chromophores and microporous channels displayed by compound 1 are expected to facilitate the sensing of small molecules [5c] .…”
Section: Resultsmentioning
confidence: 99%
“…CH 2 Cl 2 as a solvent has been commonly used in paint remover, industrial degreasing, foam production, and so on [17] . This highly volatile solvent even at room temperature has been reported as a cause of chronic toxicity, mutagenicity, and carcinogenicity for living organisms [18] . The triazine chromophores and microporous channels displayed by compound 1 are expected to facilitate the sensing of small molecules [5c] .…”
Section: Resultsmentioning
confidence: 99%
“…From the agreement of the experimental and literature adsorption isotherm data, it can be concluded that DCM does not affect the adsorption of water on the 3A molecular sieve. The DCM molecule (kinetic diameter = 3.3 Å; 33 Lennard-Jones molecular diameter = 4.7 Å 34 ) is too large to enter the 3 Å micropores of the zeolite. These results are in accordance with the findings of adsorptive drying of higher alcohols (>C4) and esters.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristic energy of adsorption can be expressed as E = β E 0 , where E 0 is the characteristic energy of adsorption for the standard substance, and β is the affinity coefficient. , The parameters of selected equilibrium models were obtained using Levenberg–Marquardt nonlinear regression algorithm.…”
Section: Adsorption Equilibrium Modelsmentioning
confidence: 99%
“…The current state of the art does not allow the theoretical prediction of thesingle-component adsorption equilibrium for any adsorbent . Therefore, for each particular adsorbate–adsorbent pair, it is necessary to measure adequate data. In the subject literature, there is a large amount of experimental data concerning the adsorption equilibrium of various pairs of adsorbate–adsorbent. However, the adsorption capacities of a particular component on the given adsorbent bed (e.g., activated carbons) may vary significantly according to adsorbent preparation method.…”
Section: Introductionmentioning
confidence: 99%